Bispectral index-guided propofol sedation during endoscopic ultrasonography - Ayana Okamoto; Ken Kamata; Takeshi Miyata; Tomoe Yoshikawa; Rei Ishikawa; Tomohiro Yamazaki; Atsushi Nakai; Shunsuke Omoto; Kosuke Minaga; Kentaro Yamao; Mamoru Takenaka; Yasutaka Chiba; et al. (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Bispectral index (BIS) monitors process and display electroencephalographic data are used to assess the depth of anesthesia. This study retrospectively evaluated the usefulness of BIS monitoring during endoscopic ultrasonography (EUS). Methods This study included 725 consecutive patients who underwent EUS under sedation with propofol. BIS monitoring was used in 364 patients and was not used in 361. The following parameters were evaluated: (1) median dose of propofol; (2) respiratory and circulatory depression; (3) occurrence of body movements; (4) awakening score >8 at the time; and (5) awakening score 2 hours after leaving the endoscopy room. Results The BIS group received a significantly lower median dose of propofol than the non-BIS group (159.2 mg vs. 167.5 mg; p=0.015) in all age groups. For patients aged ≥75 years, the reduction in heart rate was significantly lower in the BIS group than in the non-BIS group (1.2% vs. 9.1%; p=0.023). Moreover, the occurrence of body movements was markedly lower in the BIS group than in the non-BIS group (8.5% vs. 39.4%; p<0.001). Conclusions During EUS examination, BIS monitoring is useful for maintaining a constant depth of anesthesia, especially in patients 75 years of age or older.